2018
DOI: 10.3892/ijmm.2018.3603
|View full text |Cite
|
Sign up to set email alerts
|

Poligoni�Multiflori Radix enhances osteoblast formation and reduces osteoclast differentiation

Abstract: Poligoni Multiflori Radix (PMR) is a traditional Korean medicinal herb that is known to have various pharmacological effects, including antihyperlipidemic, anticancer, and anti-inflammatory effects. However, the effects of PMR on bone metabolism have not been elucidated to date. The present study aimed to investigate the in vitro and in vivo effect of PMR water extract on the regulation of osteoblast and osteoclast activity. Effects of PMR water extract on receptor activator of nuclear factor-kB ligand (RANKL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…NFATc1 is a member of the NFAT transcription superfamily and a master transcription factor in RANKL-induced osteoclastogenesis that regulates the expression of osteoclast-specific genes (Han, Lee, & Kim, 2018;Ranjan et al, 2014). Our results show that morin effec- In addition, NFATc1 is regulated by the MAPK signalling pathway, especially ERK and p38.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…NFATc1 is a member of the NFAT transcription superfamily and a master transcription factor in RANKL-induced osteoclastogenesis that regulates the expression of osteoclast-specific genes (Han, Lee, & Kim, 2018;Ranjan et al, 2014). Our results show that morin effec- In addition, NFATc1 is regulated by the MAPK signalling pathway, especially ERK and p38.…”
Section: Discussionmentioning
confidence: 69%
“…NFATc1 is a member of the NFAT transcription superfamily and a master transcription factor in RANKL‐induced osteoclastogenesis that regulates the expression of osteoclast‐specific genes (Han, Lee, & Kim, 2018; Ranjan et al, 2014). Our results show that morin effectively downregulated osteoclast differentiation and bone absorption in primary bone marrow‐derived osteoclasts by attenuating the expression of NFATc1, which is a major regulator of osteoclast differentiation (Q. Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental durations less than 2 weeks generally consisted of two to three injections of LPS ranging from 5 to 10 mg/kg body weight per injection with bones collected for ex vivo analysis within 2 weeks of the first LPS exposure. This type of experimental design consistently demonstrated negative effects of LPS on trabecular bone structure, including BV/TV, Tb.N, and Tb.Sp, in the femur ( 42‐118 ) and tibia. ( 68,119‐124 ) In studies that reported negative effects of LPS exposure on trabecular bone structure, approximately half (22/47) also reported a decreased Tb.Th in the femur ( 48,55,59,70,77,81,88,89,94,97‐101,107,108,114,117,123 ) and tibia.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we analyzed the expression of osteoblast-specific markers, such as ALP, RANKL, and osteocalcin (OCN). As shown in Supplemental Figure S3 , NAPMA treatment did not influence the expression of osteoblast differentiation ( Supplemental Figure S3A ), ALP activity ( Supplemental Figure S3B ), and differentiation markers ALP, RANKL, and osteocalcin ( Supplemental Figure S3C ) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%